Deciding Clique-Width for Graphs of Bounded Tree-Width - Espelage, Wolfgang; Gurski, Frank; Wanke, Egon (Journal of Graph Algorithms and Applications, 2003)
We show that there exists a linear time algorithm for deciding whether agraph of bounded tree-width has clique-width k for some fixed integer k. <!---->